Therapeutic Improvement of Scarring: Mechanisms of Scarless and Scar-Forming Healing and Approaches to the Discovery of New Treatments. (11th July 2010) - Occleston, Nick L.; Metcalfe, Anthony D.; Boanas, Adam; Burgoyne, Nicholas J.; Nield, Kerry; O'Kane, Sharon; Ferguson, Mark W. J.
Abstract : Scarring in the skin after trauma, surgery, burn or sports injury is a major medical problem, often resulting in loss of function, restriction of tissue movement and adverse psychological effects. Whilst various studies have utilised a range of model systems that have increased our understanding of the pathways and processes underlying scar formation, they have typically not translated to the development of effective therapeutic approaches for scar management. Existing treatments are unreliable and unpredictable and there are no prescription drugs for the prevention or treatment of dermal scarring. As a consequence, scar improvement still remains an area of clear medical need. Here we describe the basic science of scar-free and scar-forming healing, the utility of pre-clinical model systems, their translation to humans, and our pioneering approach to the discovery and development of therapeutic approaches for the prophylactic improvement of scarring in man